2021
DOI: 10.36787/jei.v15i2.583
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor-Faktor Yang Mempengaruhi Cadangan Devisa Indonesia

Abstract: Abstrak Cadangan devisa merupakan bagian penting dari perekonomian suatu negara. Besar kecilnya cadangan devisa dapat dipengaruhi oleh nilai ekspor. Tujuan dari penelitian ini yaitu menganalisis pengaruh ekspor, inflasi, BI rate, dan Utang Luar Negeri (ULN) terhadap cadangan devisa, serta menganalisis hubungan kointegrasi antara ekspor, inflasi, BI rate, dan utang luar negeri terhadap cadangan devisa. Penelitian ini menggunakan data sekunder dengan bentuk data time series. Analisis data yang digunakan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…Goods with high export capabilities can demonstrate the existence of the Indonesian state in the international scope, reflecting the stability of Indonesia's foreign exchange reserve. Therefore, exports significantly impact Indonesia's foreign exchange reserve [4] and [5]. In addition, the source of foreign exchange reserves received by the country is greater than other activities outside of exports, such as foreign loans, grants, interest, or foreign investment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Goods with high export capabilities can demonstrate the existence of the Indonesian state in the international scope, reflecting the stability of Indonesia's foreign exchange reserve. Therefore, exports significantly impact Indonesia's foreign exchange reserve [4] and [5]. In addition, the source of foreign exchange reserves received by the country is greater than other activities outside of exports, such as foreign loans, grants, interest, or foreign investment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies mention and explain the opposite, stating that exports have no relationship to foreign exchange reserves in Indonesia [4] and [5]. In addition, imports also have a significantly positive impact on the foreign exchange reserve of Indonesia [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Real interest rates and foreign reserves are associated over a long period of time, according to an auto-regressive distributed lag (ARDL) limit testing method [34]. [35] revealed that interest rates had an impact on foreign currency reserves for the period of 2016-2020 in Indonesia utilizing regression analysis of the Error Correction Model (ECM).…”
Section: Foreign Exchange Reserves With Real Interest Ratementioning
confidence: 99%
“…Cadangan devisa merupakan indikator moneter yang sangat penting untuk menunjukkan kuat atau lemahnya fundamental perekonomian suatu negara. Selain itu, cadangan devisa juga berpengaruh dalam tercapainya stabilitas moneter dan perekonomian makro suatu negara [6]. Berdasarkan data Bank Indonesia Posisi cadangan devisa Indonesia pada akhir Juli 2022 tetap tinggi sebesar 132,2 miliar dolar AS, meskipun menurun dibandingkan dengan posisi pada akhir Juni 2022 sebesar 136,4 miliar dolar AS.…”
Section: Pendahuluanunclassified